PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA KEKERASAN DALAM RUMAH TANGGA DI KEPOLISIAN RESOR KOTA BUKITTINGGI - Rianda Maisya; Firdaus '; Erdianto Effendi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
In the Indonesian criminal law is not known for peace efforts, but thereality on the ground often settling disputes through peace that criminalinvestigation of the criminal case something can be stopped, especially in thecriminal act of domestic violence (Domestic Violence). Based on this fact, thereare three problems in the formulation of this thesis, namely: First Do basicconsiderations police officers, victims and perpetrators of domestic violence penalmediation for the settlement of the criminal act of domestic violence committedagainst the husband and wife in a second ?, London Police How is theimplementation of penal mediation in resolving the Crime of Domestic Violencein the Police Bukittinggi third ?, Are the results of mediation can make domesticrelations perpetrators and victims of domestic violence to be better?The research method in this study is a qualitative research methodpossible with empirical juridical or sociological law research. Data sourcessupported by primary and secondary data sources. Data collection techniques usedwere interviews and review of literature. After the data collected subsequentqualitative analysis, and draw conclusions with motode deductive thinking is toanalyze the problems of the general form into special shapes.From the results of research and discussion, it can be concluded that, thebasic consideration of police officers, victims and perpetrators of domesticviolence penal mediation for the settlement of the criminal act of domesticviolence committed husband to wife in London police station to avoid a lengthylegal process and avoid costs that many, Implementation mediation undertaken inBukittinggi Police Unit PPA with PPA Kanit member as mediator. With domesticrelations mediation perpetrators and victims of domestic violence to be better andharmonious.Keywords: Peace Efforts - Settlement – Case – Crime